2020
DOI: 10.1037/spy0000164
|View full text |Cite
|
Sign up to set email alerts
|

Leading us to be active: A two-wave test of relationships between identity leadership, group identification, and attendance.

Abstract: Although physical activity participation has numerous physiological and psychological benefits, inactivity rates remain high, and a greater understanding of the factors that drive participation is needed. Growing evidence indicates that (1) the strength of individuals' social identification as a member of a particular physical activity group (e.g., an exercise group or sports team) is positively associated with their group-relevant participation, and (2) physical activity leaders (e.g., exercise group leaders,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 46 publications
2
26
2
Order By: Relevance
“…Estabrooks et al ( 2004 : 233) have previously noted how the instructor is ‘the most important determinant of participation in physical exercise groups’. Studies of physical presence exercise classes have demonstrated the importance of the instructor in creating cohort experiences and a sense of group identity (Stevens et al 2020 ) and creating confidence and empowering messaging, both of which are important for continued engagement (Chemers et al 2000 ). Our study suggests that importance of the instructor carries through into Zoom space although it may demand more explicit performance than in the studio.…”
Section: Discussionmentioning
confidence: 99%
“…Estabrooks et al ( 2004 : 233) have previously noted how the instructor is ‘the most important determinant of participation in physical exercise groups’. Studies of physical presence exercise classes have demonstrated the importance of the instructor in creating cohort experiences and a sense of group identity (Stevens et al 2020 ) and creating confidence and empowering messaging, both of which are important for continued engagement (Chemers et al 2000 ). Our study suggests that importance of the instructor carries through into Zoom space although it may demand more explicit performance than in the studio.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is important to reiterate that, from a social identity perspective, effective leadership is not solely contingent on leaders’ identity entrepreneurship (i.e., their capacity to create a shared sense of identity among group members) but also on their capacity to represent and advance that identity, and help embed it in reality. As such, there is considerable scope for future research to explore both the distinct and combined effects of real-world sport and exercise leaders engaging in the four facets of identity leadership, particularly in light of recent evidence for context-specific differences in the relative importance of sporting leaders engaging in each of these [83].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the social identity approach provides crucial and unique social processes to understand and influence physical activity participation [5][6][7]. While the social identity approach has been applied across a variety of contexts including within organisations [8], and sport [5,9], research with regard to its relevance to exercise remains limited (exceptions [6,7]). The social identity approach comprises two theories; social identity theory [10] and self-categorisation theory [11].…”
Section: The Social Identity Approachmentioning
confidence: 99%
“…The application of the social identity approach to physical activity has garnered interest in how leaders (e.g. class instructors) in these settings may influence physical activity behaviour [7,9,20,26]. Exercise leaders (i.e.…”
Section: The Social Identity Approach To Leadershipmentioning
confidence: 99%
See 1 more Smart Citation